PENERAPAN SANKSI TINDAK PIDANA YANG DILAKUKAN OLEH PEJABAT NEGARA DALAM TINDAK PIDANA SUAP DITINJAU DARI UNDANG-UNDANG TINDAK PIDANA KORUPSI (STUDI KASUS PUTUSAN NOMOR 64/PID.SUS.K/2013/PN.MDN) - Mohamad Hadi Sutjipto (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
One of the most fertile and systemic areas of corruption is in the field of government procurement of goods/services. This sector has a very large influence in building economic power in a country, and also the vulnerability of this sector to the risk of administrative malls and corrupt acts that harm the country's finances. Throughout the establishment of the Corruption Eradication Commission (KPK), no less than 50 (fifty) cases related to irregularities in the procurement of government goods / services in which cases resulted in state losses of 35 (thirty-five) percent of the total project value. The problem is how the influence of officials to bidders who give bribes that lead to criminal acts of corruption? And what is the authority of officials in making policies in the procurement of goods and services in legislation? The research method, this research is included in the form of normative juridical research that is research that emphasizes the use of legal norms in writing. In conclusion, the influence of Officials on Tender Participants Who Gives Bribes, Causing Corruption. Entrepreneurs use the influence of central officials to move / persuade regional heads to intervene in the procurement process in order to win certain entrepreneurs/partners and raise prices or the value of contracts and the intended entrepreneurs / partners give some money to central or regional officials. The entrepreneur influences the regional head / regional official to intervene in the procurement process so that certain partners are won in a tender or appointed directly and the price of goods / services is raised (mark-up), then the rest is divided up.